International Financial Crises - Rudi Dornbusch; Stanley Fischer (Center for Economic Studies and ifo Institute (CESifo), 2003)
Our friend and colleague Rüdiger Dornbusch passed away before he was able tocomplete his book based on the Munich Lectures in Economics that he gave inNovember 17, 1998, at the Center for Economic Studies of Ludwig-Maximilians-Universität.The lectures contain a fascinating overview of the mechanics andhistory of international financial crises showing the breadth and ingenuity of thiseminent scholar. The lectures were lively and provocative, full of importantinsights and observations. Interestingly enough, Dornbusch expressed asubstantial mistrust in the actions of political decision makers, supervisoryagencies and central banks in the game that leads to the crisis and even collapse offinancial systems, and he advocated supranational supervisory actions as aremedy. CES has decided to prepare a transcript of the lectures, which are also available inthe Internet as full length-videos. I am grateful to Paul Kremmel for hisassistance.
Keywords: 330